Antiepileptic Drug Nonadherence and Its Predictors among People with Epilepsy - Asmamaw Getnet; Solomon Meseret Woldeyohannes; Lulu Bekana; Tesfa Mekonen; Wubalem Fekadu; Melak Menberu; Solomon Yimer; Adisu Assaye; Amsalu Belete; Habte Belete (Behavioural Neurology)
Introduction. Antiepileptic drugs are effective in the treatment of epilepsy to the extent that about 70% of people with epilepsy can be seizure-free, but poor adherence to medication is major problem to sustained remission and functional restoration. The aim of this study was to assess the prevalence and associated factors of antiepileptic drug nonadherence. Methods. Cross-sectional study was conducted on 450 individuals who were selected by systematic random sampling method. Antiepileptic drug nonadherence was measured by Morisky Medication Adherence Scale (MMAS) and logistic regression was used to look for significant associations. Result. The prevalence of AEDs nonadherence was 37.8%. Being on treatment for 6 years and above [AOR = 3.47, 95% CI: 1.88, 6.40], payment for AEDs [AOR = 2.76, 95% CI: 1.73, 4.42], lack of health information [AOR = 2.20, 95% CI: 1.41,3.43], poor social support [AOR = 1.88, 95%, CI: 1.01, 3.50], perceived stigma [AOR = 2.27, 95% CI: 1.45, 3.56], and experience side effect [AOR = 1.70, 95% CI: 1.06, 2.72] were significantly associated with antiepileptic drug nonadherence. Conclusion. More than one-third of people with epilepsy were not compliant with their AEDs. Giving health information about epilepsy and its management and consequent reduction in stigma will help for medication adherence.